Outcast Dead - Griffiths, Elly (Boston : Mariner Books, a division of Houghton Mifflin Harcourt, 2015)
"Forensic archaeologist Ruth Galloway uncovers the bones of a Victorian murderess while a baby snatcher threatens modern-day Norfolk in this exciting new entry in a beloved series. Every year a ceremony is held in Norwich for the bodies in the paupers' graves: the Service for the Outcast Dead. Ruth has a particular interest in this year's proceedings. Her recent dig at Norwich Castle turned up the body of the notorious Mother Hook, who was hanged in 1867 for the murder of five children. Now Ruth is the reluctant star of the TV series Women Who Kill, working alongside the program's alluring history expert, Professor Chet Bruce. DCI Harry Nelson is immersed in the case of three children found dead in their home. He is sure that the mother is responsible. Then another child is abducted and a kidnapper dubbed the Childminder claims responsibility. Are there two murderers afoot, or is the Childminder behind all the deaths? The team must race to find out--and the stakes couldn't be any higher when another child goes missing."--
108704
Keywords: Galloway, Ruth -- (Fictitious character); Women forensic anthropologists -- Fiction; Missing children; Murder -- Investigation; Norfolk (England) -- Fiction; Mystery fiction